Handicraft Business Opportunities Using Mineral Glass Water: an Innovative Student Enterprise Focused on Eco-Friendly Products in Selangor, Malaysia - Purnama, Hukma Ratu; Ikhtiarani, Kirana; Sudarman; Putri, Masita Nairul Aulia; Hasanah, Huswatun (MultiTech Publisher, 2024)
Used plastic cups are inorganic waste that is difficult to decompose and often discarded because they are considered useless. However, if managed properly, used plastic cups can be repurposed into various useful and aesthetically valuable craft products. Examples of crafts that can be made include fruit baskets, hijab hangers, decorative lamps, and flowers made from plastic cups. This recycling process not only helps reduce environmental pollution but also provides opportunities to create innovative and beneficial products. This activity is part of an international Community Service (PkM) program conducted by Universitas Muslim Indonesia (UMI) at Universiti Kebangsaan Malaysia (UKM). The program aims to provide participants at UKM with an understanding of the importance of entrepreneurship and creativity in managing plastic waste. Through this training, participants are expected to develop an entrepreneurial spirit, enhance their courage in facing challenges, and innovate to create solutions that are beneficial to both the environment and society